Overcoming barriers to optimal drug dosing during ECMO in critically ill adult patients - Cheng, Vesa; Abdul-Aziz, Mohd Hafiz; Roberts, Jason A.; Shekar, Kiran (Taylor & Francis, 2019)
Introduction: One major challenge to achieving optimal patient outcome in extracorporeal membrane oxygenation (ECMO) is the development of effective dosing strategies in this critically ill patient population. Suboptimal drug dosing impacts on patient outcome as patients on ECMO often require reversal of the underlying pathology with effective pharmacotherapy in order to be liberated of the life-support device.